2016
DOI: 10.1177/0300985815626574
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin and Osteonectin Expression in Canine Osteosarcoma

Abstract: Osteosarcoma (OSA) is a malignant heterogeneous primary bone tumor responsible for up to 90% of all primary bone tumors in dogs. In this study, osteocalcin (OC) and osteonectin (ON) immunoreactivity was evaluated in 23 canine OSAs, 4 chondrosarcomas, 4 fibrosarcomas, 2 hemangiosarcomas, and 4 histiocytic sarcomas. The effects of three different decalcification agents (ethylenediaminetetraetic acid [EDTA], formic acid and hydrochloric acid [HCl]) on the immunoreactivity for OC and ON was also assessed. Immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…Osteocalcin was detected in most but not all tumor cell lines, which is in agreement with findings from immunohistochemical assays of primary tumor tissue (40,42), and studies of human OSA (31). Osteocalcin was inconsistently detected in primary OSA tissues (40), and may be more consistent in clonal cell lines. Osteocalcin was inconsistently detected in primary OSA tissues (40), and may be more consistent in clonal cell lines.…”
Section: Discussionsupporting
confidence: 87%
“…Osteocalcin was detected in most but not all tumor cell lines, which is in agreement with findings from immunohistochemical assays of primary tumor tissue (40,42), and studies of human OSA (31). Osteocalcin was inconsistently detected in primary OSA tissues (40), and may be more consistent in clonal cell lines. Osteocalcin was inconsistently detected in primary OSA tissues (40), and may be more consistent in clonal cell lines.…”
Section: Discussionsupporting
confidence: 87%
“…The microscopic diagnosis of osteosarcoma can be challenging, especially when a small sample has been sent for the histopathological examination or cytology is the only diagnostic method used (Wehrle-Martinez et al 2016). Nevertheless, cytology is considered an accurate method of presurgical diagnosis of canine osteosarcoma (Baker and Lumsden 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The antiosteonectin antibody is poorly sensitive and can react with various cell types including active osteoblasts, immature osteocytes, fibroblasts, and epithelial cells (PARHAM, 2015;WEHRLE-MARTINEZ et al, 2016). Anti-osteopontin antibody also has low sensitivity, and although studies have shown expression in osteosarcomas, this antibody also presents immunoreaction in the epithelium of the gastrointestinal tract, gallbladder, pancreas, urinary, and reproductive tracts, salivary and sweat glands, as well as vascular endothelial cells, macrophages, and myoepithelial cells, and there is no immunostaining.…”
Section: Intestinal Osteosarcomamentioning
confidence: 99%
“…Anti-osteopontin antibody also has low sensitivity, and although studies have shown expression in osteosarcomas, this antibody also presents immunoreaction in the epithelium of the gastrointestinal tract, gallbladder, pancreas, urinary, and reproductive tracts, salivary and sweat glands, as well as vascular endothelial cells, macrophages, and myoepithelial cells, and there is no immunostaining. in hematopoietic neoplasms (PARHAM, 2015;WEHRLE-MARTINEZ et al, 2016). The anti-osteocalcin antibody reacts with osteocytes of adult bone and presents positive immunostaining in 66.6% of cases of low-grade, well-differentiated osteosarcomas; therefore it is more specific when compared to osteonectin and osteopontin (WEHRLE-MARTINEZ et al, 2016).…”
Section: Intestinal Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation